Retrospective analysis of the incidence of intracranial physiological calcifications with cone beam computed tomography - Melis Mısırlı Gülbeş; Berfu Çerci Ongun; Nimet İlke Akçay; Kaan Orhan (Selcuk Dental Journal)
Background: The purpose of the present study was to evaluate the incidence of physiologic intracranial calcifications detected in cone beam computed tomography (CBCT) images of in a group Turkish Cypriot population.Methods: The CBCT scans of the full head of 100 patients that met our ascertainment criteria were evaluated retrospectively for the presence of physiological intracranial calcifications.Results: Intracranial calcification was found in 71 cases of 100 patients. The most common site of calcification was habenular with 48% followed by %14 caroticoclinoid ligament, 13% interclinoid ligament and 8% choroid plexus. In our study, petroclinoid ligament calcification was not observed at all.Conclusion: CBCT is widely used in many scientific investigations and anatomical studies. Intracranial physiological calcification are frequent incidental findings of CBCT scans.KEYWORDS